2022
DOI: 10.1021/acsnano.2c01254
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Infrared Response and Orientation-Dependent Strain-Tuning of the Electronic Structure in Nb2SiTe4

Abstract: Two-dimensional materials with tunable in-plane anisotropic infrared response promise versatile applications in polarized photodetectors and field-effect transistors.Black phosphorus is a prominent example. However, it suffers from poor ambient stability. Here, we report the strain-tunable anisotropic infrared response of a layered material Nb2SiTe4, whose lattice structure is similar to the 2H-phase transition metal dichalcogenides (TMDCs) with three different kinds of building units. Strikingly, some of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…Calculation results by Chaves et al showed that, although larger than the usual trion binding energy in TMDCs, even the trion binding energy in suspended monolayer BP is only ∼51 meV, and decreases to ∼34 meV in supported BP, which is much smaller than the claim by Yang et al [138] . Due to the discrepancy, the validity [41,42,125,126] 8.2(x), 2.3(y) [133] AC(x) Multi-interband w 0.3-0.45 [102,106,108] , 0.9 [104] Bulk / MX (M = Ge, Sn; X = S, Se) GeS 1L w/o ∼0.7-1.2 [34,128,129] 6.7(x), 4.5(y) [34] AC(x) Multi-valley exciton w ∼0.6 [129] Bulk / <0.1 GeSe 1L w/o ∼0.3-0.4 [34,130,129] 21.2(x), 15.4(y) [34] w ∼0.2 [129] Bulk / <0.1 SnS 1L w/o ∼0.5-0.9 [34,128] 15.1(x), 15.1(y) [34] Bulk / <0.1 SnSe 1L w/o ∼0.3 [34,130] 27.3(x), 25(y) [34] Bulk / <0.1…”
Section: Excitons In Bpmentioning
confidence: 99%
See 4 more Smart Citations
“…Calculation results by Chaves et al showed that, although larger than the usual trion binding energy in TMDCs, even the trion binding energy in suspended monolayer BP is only ∼51 meV, and decreases to ∼34 meV in supported BP, which is much smaller than the claim by Yang et al [138] . Due to the discrepancy, the validity [41,42,125,126] 8.2(x), 2.3(y) [133] AC(x) Multi-interband w 0.3-0.45 [102,106,108] , 0.9 [104] Bulk / MX (M = Ge, Sn; X = S, Se) GeS 1L w/o ∼0.7-1.2 [34,128,129] 6.7(x), 4.5(y) [34] AC(x) Multi-valley exciton w ∼0.6 [129] Bulk / <0.1 GeSe 1L w/o ∼0.3-0.4 [34,130,129] 21.2(x), 15.4(y) [34] w ∼0.2 [129] Bulk / <0.1 SnS 1L w/o ∼0.5-0.9 [34,128] 15.1(x), 15.1(y) [34] Bulk / <0.1 SnSe 1L w/o ∼0.3 [34,130] 27.3(x), 25(y) [34] Bulk / <0.1…”
Section: Excitons In Bpmentioning
confidence: 99%
“…(c) Illustration of interband transitions at normalΓ point of BP. (d) Photocurrent spectra of thin TiS3 (15 nm) (left) [99] and absorption spectra of thin Nb2SiTe4 (18 nm) (right) [102] . (e) Layer-dependent bandgap and interband transitions.…”
Section: Optical Properties Of Low Symmetry 2d Materialsmentioning
confidence: 99%
See 3 more Smart Citations